2015
DOI: 10.1007/s40846-015-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Contrast Enhancement of Brain MR Images Using Hierarchical Correlation Histogram Analysis

Abstract: Parkinson’s disease is a progressive neurodegenerative disorder that has a higher probability of occurrence in middle-aged and older adults than in the young. With the use of a computer-aided diagnosis (CAD) system, abnormal cell regions can be identified, and this identification can help medical personnel to evaluate the chance of disease. This study proposes a hierarchical correlation histogram analysis based on the grayscale distribution degree of pixel intensity by constructing a correlation histogram, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…It also adjusts the initial pixel quantities with accuracy of 87.1% which increases the contrast between the images. The dynamic model on the pixel similarity functions for optimization is developed by Chiao et al [5]. MRI differentiation is implemented to region of interest.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It also adjusts the initial pixel quantities with accuracy of 87.1% which increases the contrast between the images. The dynamic model on the pixel similarity functions for optimization is developed by Chiao et al [5]. MRI differentiation is implemented to region of interest.…”
Section: Related Workmentioning
confidence: 99%
“…The isolateral filtering technique is used in this research work which works directly on pixels taken into consideration of the neighbourhood pixel values depending on the intensity of the pixel values. It works in spatial domain [4], [5] to remove the noise vectors in brain tumor image. This filter primarily depends on the Gaussian distributed values and also the distance between subsequent pixel values with variable intensities.…”
Section: Algorithm 1: Isolateral Filtermentioning
confidence: 99%
“…Thus, the median filter [31] is applied to reduce the ambiguity between a bone structure and fracture, as shown in Figure 13a. Then, the automatic contrast enhancement [32] is implemented to obtain a clear fragment separation in bone structure, as shown in Figure 13b. The image histogram, which shows the relationship between the gray level and the corresponding frequency, can be expressed as:…”
Section: Build Contour Hierarchiesmentioning
confidence: 99%
“…In preprocessing, contrast enhancement of multicenter data image is an important challenge. It was shown that a high-contrast medical image could lead to a better interpretation of the different adjacent tissues in the imaged body part [19,20]. Accordingly, the resulting enhanced image, which is in terms of signal intensities of different tissues, can facilitate the automated segmentation, feature extraction, and classification of these tissues.…”
Section: Related Workmentioning
confidence: 99%